The Impact of Economic Theories on the Economic Behavior of Teacher Education Students - Oloieru, Anastasia (Didactica Danubiensis, 2022)
Currently economics is regarded as a moral science due to the expansion of phenomena such as excessive consumption, irrationality, etc. Despite the fact that classical economics revolves around homo economicus researchers in the field of behavioral economics have noted that people are not rational beings and systematically make certain errors. The article defines economic behavior, explains the differences between rational and irrational behavior and characterizes the behavioral errors that ordinary people make in real life. Also it is highlighted how the knowledge of economic theories helps future specialists in education to achieve high professional performance and personal development.